(untitled) (VETERINARIA, 2020)
In the present study, for the first time we investigated the genetic diversity among horse breeds from Bosnia and Herzegovina: potential Bosnian and Herzegovinian mountain horse, Arabian horse, Thoroughbred horse and crossbreeds, with special emphasis on the gene pool of potential Bosnian and Herzegovinian mountain horse. In total, 138 animals were genotyped for 17 microsatellite loci. Compared to the other breeds, potential Bosnian and Herzegovinian mountain horse showed quite a high genetic variability. The mean number of alleles was 14.1765. The average observed heterozygosity was 0.6589 and the expected heterozygosity was 0.8451. The mean value of polymorphic information content was 0.8286. The results of AMOVA test showed 8.44% of genetic variation among populations. The highest genetic variation within population was showed by potential Bosnian and Herzegovinian mountain horse (27.13). The same breed showed the highest individual variation (17.35). Overall FST value showed high level of the genetic differentiation among breeds (8.87%), and the pairwise FST values were all significant. Highest inter-group genetic differentiation was observed among Arabian horse and Thoroughbred horse (groups of pure breeds) and potential Bosnian and Herzegovinian mountain horse. The results show that the potential Bosnian and Herzegovinian mountain horse has a high within breed variability, more than could be expected. In the gene pool of potential Bosnian and Herzegovinian mountain horse is present a part of the gene pool of other breeds. Also, these results show that there are very good preconditions for the revitalization of the gene pool of potential Bosnian and Herzegovinian mountain horse.